2021
DOI: 10.3390/jcm10122726
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptides and High-Sensitive Troponin I as COVID-19 Survival Factors: Which One Is the Best Performer?

Abstract: Increased concentrations of B-type natriuretic peptide (BNP), N-terminal pro-B-type natriuretic peptide (NT-proBNP) and high-sensitivity troponin I (HsTnI) in COVID-19 patients have already been reported. The aim of this study is to evaluate which of these common markers of cardiac disease is the most useful predictor of fatal outcome in COVID-19 patients. One hundred and seventy-four patients affected with COVID-19 were recruited, and markers of cardiac disease and the clinical history of the patients were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In line with other reported data, BNP did not show a predictive value for the outcomes in noncritically ill survivors versus non-survivors [ 39 ]. This may be explained by the fact that, compared to BNP, NT-pro BNP and hs-TnI appeared to be better performers in predicting mortality for inpatients [ 9 , 39 ]. NT-pro BNP acts as a more sensitive prognostic biomarker after admission [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with other reported data, BNP did not show a predictive value for the outcomes in noncritically ill survivors versus non-survivors [ 39 ]. This may be explained by the fact that, compared to BNP, NT-pro BNP and hs-TnI appeared to be better performers in predicting mortality for inpatients [ 9 , 39 ]. NT-pro BNP acts as a more sensitive prognostic biomarker after admission [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In critically ill COVID-19 patients, defined as individuals with respiratory failure, septic shock, and/or multiple organ dysfunction [ 7 ], the use of cardiac biomarkers for risk stratification proved to be useful [ 8 ], since elevated troponin is associated with greater mortality in COVID-19, and N-terminal pro-B-type natriuretic peptide (NT-pro BNP) is strongly and independently associated with in-hospital mortality and other complications in patients with and without heart failure [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a sign of myocardial stress, NT-proBNP increase could be due to a cytokine storm in response to the infection trigger and to the direct action of the virus on the heart walls [ 35 , 36 ]. More accurately, NT-proBNP appears as the best representative prognosis biomarker in COVID-19 disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In SARS-CoV-2 infection, the dynamic changes of NT-proBNP, CRP, and cTn concentrations are basically related to the extent of the inflammatory response, tissue injury, and functional impairment. Guo et al reported higher levels of natriuretic peptides in severe forms of COVID-19 pneumonia, especially in deceased patients [ 26 ], while De Falco et al showed that the prognosis value of NT-proBNP is similar to cTn, specifically for mortality risk stratification [ 136 ].…”
Section: Biomarkers In the Diagnosis And Prognosis Of Acute Myocardia...mentioning
confidence: 99%